The association of the composite IL-1genotype with periodontitis progression and/or treatment outcomes: a systematic review - G. Huynh-Ba (Blackwell Synergy, 2007)
Background: Genetically transmitted traits such as cytokine gene polymorphisms may accentuate the host inflammatory response to the bacterial challenge and influence susceptibility to periodontitis. Objective: To systematically review the evidence of an association between the interleukin-1 (IL-1) composite genotype, i.e. presence of the allele 2 in the gene clusters IL-1A-889 and in IL-1B 13953, and periodontitis progression and/or treatment outcomes. Material and Methods: Based on the focused question, a search was conducted for longitudinal clinical trials comparing progression of periodontitis and/or treatment outcomes in IL-1 genotype-positive (carrying allele 2) and IL-1 genotype-negative (not carrying allele 2) subjects. A search in the National Library of Medicine computerized bibliographic database MEDLINE and a manual search were performed. Selection of publications, extraction of data and validity assessment were made independently by two reviewers. Results: The search provided 122 titles of which 11 longitudinal publications were included. The heterogeneity of the data prevented the performance of a meta-analysis. While findings from some publications rejected a possible role of IL-1 composite genotype on progression of periodontitis after various therapies, other reported a prognostic value for disease progression of the positive IL-1 genotype status. When assessed on a multivariate risk assessment model, several publications concluded that the assessment of the IL-1 composite genotype in conjunction with other covariates (e.g. smoking and presence of specific bacteria) may provide additional information on disease progression. The small sample size of the available publications, however, requires caution in the interpretation of the results.